(untitled) (Orfeu, 2022)
This text presents the idea of Musicking performances as performances of existence. This idea was developed based on performance conceptions from an artistic and anthropological point of view, drawing connections with musical performances and educational ideas. It was structured through field research, which included online interviews with twelve cello teachers from eight musical spaces for beginning students’ cello teaching and learning in Brazil. This study uses ethnography, autoethnography, and cartography, and considers performances with musical practices as pedagogical processes of representation of ways of existing that extend to everyday life. Ideas are approached as processes in becoming, typical of musicking practices in the action of breaking themselves up and building again under new configurations.